2019
DOI: 10.1002/slct.201902134
|View full text |Cite
|
Sign up to set email alerts
|

New Porous High Surface Area, TiO2 Anatase/SAPO‐35 Mild Brønsted Acidic Nanocomposite: Synthesis, Characterization and Studies on it's Enhanced Photocatalytic Activity.

Abstract: type microporous silico alumino phosphate SAPO-35 are synthesized by using hydrothermal method. TiO 2 /SAPO-35 nanocomposites were prepared by solgel method with different weight ratios. The synthesized materials were characterized by various analytical techniques such as PXRD, SEM/EDAX, TG/DTA, BET-Surface area, FT-IR, UV-Vis, XPS, MAS-NMR and photocatalytic study. From PXRD results it clearly evidenced that, the TiO 2 anatase peaks and SAPO-35 combined peaks are in the composite. The spherical shaped TiO 2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…Figure represents the PXRD patterns of the SAPO and promoter samples, and it can be observed from Figure that the peaks at 2θ values of 10.9, 13.3, 17.3, 21.9, 26.6, and 32.3° correspond to Miller indices of (012), (110), (104), (024), (220), and (134) planes, respectively. As per the literature [JCPDS: 51–0052], it is confirmed that the synthesized SAPO-35 has a Levyne-type hexagonal crystalline structure. , Furthermore, the relative crystallinity of each sample was calculated using the most prominent peak in the corresponding PXRD pattern, which was observed at a 2θ value of 21.9° corresponding to the (024) plane. In order to calculate the relative crystallinity of the synthesized samples, the relative crystallinity of the standard sample prepared at 360 h was taken as 100%.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Figure represents the PXRD patterns of the SAPO and promoter samples, and it can be observed from Figure that the peaks at 2θ values of 10.9, 13.3, 17.3, 21.9, 26.6, and 32.3° correspond to Miller indices of (012), (110), (104), (024), (220), and (134) planes, respectively. As per the literature [JCPDS: 51–0052], it is confirmed that the synthesized SAPO-35 has a Levyne-type hexagonal crystalline structure. , Furthermore, the relative crystallinity of each sample was calculated using the most prominent peak in the corresponding PXRD pattern, which was observed at a 2θ value of 21.9° corresponding to the (024) plane. In order to calculate the relative crystallinity of the synthesized samples, the relative crystallinity of the standard sample prepared at 360 h was taken as 100%.…”
Section: Resultssupporting
confidence: 68%
“…As per the literature [JCPDS: 51−0052], it is confirmed that the synthesized SAPO-35 has a Levyne-type hexagonal crystalline structure. 18,27 Furthermore, the relative crystallinity of each sample was calculated using the most prominent peak in the corresponding PXRD pattern, which was observed at a 2θ value of 21.9°corresponding to the (024) plane. In order to calculate the relative crystallinity of the synthesized samples, the relative crystallinity of the standard sample prepared at 360 h was taken as 100%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of well-matched, coinciding band-structures, photogenerated excitons effectively separated and migration towards the surface of SMO/G-CN-10 composite photocatalyst leads to the enhancement in photocatalytic activity. Plausible photocatalytic degradation mechanism of RhB dye pollutants under sunlight for SMO/G-CN-10 composite photocatalyst is represented by the following equations (5)(6)(7)(8)(9). SMO=G…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…These pollutants are hazardous to human and animal health even at their extreme trace concentration. [4][5][6] Hitherto, several methods such as photocatalytic degradation, membrane filtration, adsorption, flocculent precipitation, biological treatment, and so on were adopted for removal of water pollutants were adopted. [7][8][9][10][11] In comparison to these methods, the photocatalytic degradation method is widely preferred in the recent years, This is because, it is cost effective method as it employs the utilization of inexhaustible solar radiation as energy source and is found to be efficient, simple and convenient method.…”
Section: Introductionmentioning
confidence: 99%